Tracing a historical development of conspiracy theory networks on the web: The hyperlink network of vaccine hesitancy on the Danish web 2006–2015. (August 2022) - Brügger, Niels
This article investigates the vast field of conspiracy theories by focusing on the example of conspiracy theories related to vaccine hesitancy. Conspiracy theories have been with us for a long time, and as any other type of semantic content they spread by travelling through media. Therefore, if one wants to understand how conspiracy theories proliferate, it is relevant to investigate the media roads by which they travel and that each offer different opportunities for establishing connections. It is obvious that within the last three decades the advent of digital media has opened up new road systems to support conspiracy theories' getting around. This article focuses on one such road system, the World Wide Web, and how the hyperlink networks on the Danish web related to conspiracy theories and vaccine hesitancy have developed from 2006 to 2015. The article aims at (1) contributing to the development of methods that enables such a study, and (2) providing results about how these hyperlink networks have developed. The network analysis reveals that the potential exchange of ideas about vaccination between experts and non-experts is not facilitated by the media material structures in either of the years, since almost no links exist between the two actor types, at least not on the physical performative level of hyperlinks. Experts are connected, but non-experts as a whole tend to function as an archipelago of isolated islands—isolated from the experts, and by and large isolated from each other. This tendency has remained almost the same throughout the investigated period. News media that one could expect to function as brokers connecting experts and non-experts are not particularly well-connected in the network and apparently do not mediate between actor types.